2014
DOI: 10.1109/jbhi.2013.2286697
|View full text |Cite
|
Sign up to set email alerts
|

Drift-Free Position Estimation for Periodic Movements Using Inertial Units

Abstract: Latest advances in microelectromechanical systems have made inertial units (IUs) a powerful tool for human motion analysis. However, difficulties in handling their output signals must be overcome. The purpose of this study was to develop the novel "PB-algorithm" based on polynomial data fitting, splines interpolation, and the wavelet transform, one after the other, to cancel drift disturbances in position estimation for periodic movements. High-accuracy position measurements from an optical system (Vicon Nexus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…derived from the HoloLens and Opal sensors, we found good to excellent signal agreement for the majority of STS and TUG measures (Xcor 0.74-0.99, NRMSE ~10%), with better signal agreement observed in STS task, as each sit-to-stand cycle allows for displacement calibration adjustment (Zero Displacement Update) [24]. For sensor signal comparison in TUG task, however, due to the integration and drift error associated with IMU sensor and lack of viable calibration during the walking period (10s or longer), the vertical displacement derived from IMU sensors was biased in comparison to HoloLens output ( Fig.2e), resulting unsatisfactory NRMSE measures (14.07-19.56%).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…derived from the HoloLens and Opal sensors, we found good to excellent signal agreement for the majority of STS and TUG measures (Xcor 0.74-0.99, NRMSE ~10%), with better signal agreement observed in STS task, as each sit-to-stand cycle allows for displacement calibration adjustment (Zero Displacement Update) [24]. For sensor signal comparison in TUG task, however, due to the integration and drift error associated with IMU sensor and lack of viable calibration during the walking period (10s or longer), the vertical displacement derived from IMU sensors was biased in comparison to HoloLens output ( Fig.2e), resulting unsatisfactory NRMSE measures (14.07-19.56%).…”
Section: Discussionmentioning
confidence: 64%
“…STS and TUG tests, the gravity corrected vertical (VT) acceleration data from Opal sensors were double integrated over time to obtain the vertical displacement, with drift and integration error corrected using 1) a high pass filter (4th order Butterworth, 0.1Hz)[23] and 2) drift correction under the assumption that participants reach the same height when they make contact with the chair (zero displacement update-ZDU)[24]. The processed VT displacement from HoloLens and Opal sensors was then time-aligned using cross correlation analysis (calculating the similarity and time lag between signal).…”
mentioning
confidence: 99%
“…The works carried out by the researchers in [19]- [25] confirm the negative effect of drift in applications that use IMU sensors to derive displacement. Various solutions were proposed in these studies to minimize the effect of this drift in their respective applications.…”
Section: Introductionmentioning
confidence: 78%
“…This technique works by estimating an error offset on the evaluated displacement, based on a mathematical model that integrates the measurements obtained from other related sensors. The correction models in [19], [21] are targeted to applications where the motion of the object is periodic, and its theory basically relies on pre-existing knowledge of the expected frequencies or band.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the MEMD is superior to other signals processing method such as Fourier and wavelet transformation [20,30,31]. Moreover, it is demonstrated that the MEMD is clearly suitable for processing non-deterministic and non-stationary electrophysiological signals because the MIMFs decomposed by MEMD can reflect the local characteristics of signal at any time [32].…”
Section: A Removing Eoas From Simulated Eeg Signalsmentioning
confidence: 99%